Perfectionism, conscientiousness, and neuroticism: Does age matter?. (April 2021) - Robinson, Anthony; Divers, Ross; Moscardini, Emma; Calamia, Matthew
Abstract: Research has linked dimensions of perfectionism and personality traits included in the five-factor model (FFM), such as conscientiousness and neuroticism. There has been very little research, however, on the relationship between perfectionism and FFM facets in older adults (i.e., age 60+). This is of particular importance given that previous research suggests that as individuals age, the relationship between perfectionistic strivings and conscientiousness weakens, and the relationship between perfectionistic strivings and neuroticism increases. The present study aimed to examine the moderating effect of age on the perfectionism-conscientiousness and perfectionism-neuroticism link. In addition, a secondary aim was to examine differences in perfectionism levels amongst young adults and older adults. Measures of perfectionism and the FFM facets, conscientiousness, and neuroticism, were administered to a sample of undergraduates ( n = 587) and older adults ( n = 313). Age was found to moderate the relationship between personal standards and conscientiousness only. Differences in perfectionism levels as well conscientiousness and neuroticism were observed. More specifically, undergraduates were higher on perfectionistic strivings and neuroticism. Research and clinical implications are discussed. Highlights: Age moderated the relationship between personal standards and conscientiousness. Undergraduates were higher on perfectionistic strivings and neuroticism. Older adults were higher on conscientiousness.